Alright, lets get started.
Suppose the smaller integer = n
So, larger integer will be = n+2
3 times of larger integer will be = ![3(n+2)](https://tex.z-dn.net/?f=3%28n%2B2%29)
smaller integer is added into this , so
![n +3 (n+2)](https://tex.z-dn.net/?f=n%20%2B3%20%28n%2B2%29)
The result is 2 less than 5 times of smaller integer, so
![5n - 2](https://tex.z-dn.net/?f=5n%20-%202)
Both are equal so,
![n + 3 (n+2) = 5n - 2](https://tex.z-dn.net/?f=n%20%2B%203%20%28n%2B2%29%20%3D%205n%20-%202)
![n + 3n + 6 = 5n - 2](https://tex.z-dn.net/?f=n%20%2B%203n%20%2B%206%20%3D%205n%20-%202)
Rafael makde the mistake that he didn't put the larger integer into parenthesis like (n+2) , so three times will be 3 n + 6 as he got 3n + 2
So, the correct equation is
![n +3n +6 = 5n - 2](https://tex.z-dn.net/?f=n%20%2B3n%20%2B6%20%3D%205n%20-%202)
Solving the equation
![4n + 6 = 5n - 2](https://tex.z-dn.net/?f=4n%20%2B%206%20%3D%205n%20-%202)
![n = 8](https://tex.z-dn.net/?f=n%20%3D%208)
So, saller integer is 8 and larger integer is ![8 + 2 = 10](https://tex.z-dn.net/?f=8%20%2B%202%20%3D%2010)
So, both integers are 8 and 10. : Answer
Hope it will help :)